Molecular signatures define BAP1-altered meningioma as a distinct CNS tumor with deregulation of Polycomb repressive complex target genes - Sievers, Philipp; Arora, Sonali; Hielscher, Thomas; Savran, Dilan; Schrimpf, Daniel; Banan, Rouzbeh; Vonhören, David; Pusch, Stefan; Sill, Martin; Appay, Romain; Wirsching, Hans-Georg; Hortobagyi, Tibor; et al. (Neuro-Oncology, 2025)
Meningiomas are the most common primary intracranial neoplasms, with highly variable patient outcomes. While most meningiomas are benign, a significant subset recurs postoperatively, presenting substantial treatment challenges. BAP1 gene inactivation has been suggested as a marker for aggressive meningiomas, although its precise molecular and clinical roles remain poorly understood.To comprehensively investigate BAP1-altered meningiomas, we used six meningiomas with known BAP1 alterations as a discovery set. Genome-wide DNA methylation profiling of these samples, along 11 151 reference meningiomas, identified a distinct molecular cluster (n = 42) using unsupervised visualization approaches. These tumors were further characterized by DNA/RNA sequencing, histopathological examination, and a retrospective review of clinical data, compared to reference meningioma cohorts, providing a thorough characterization of this rare tumor subtype.Our integrative analysis revealed BAP1-altered meningiomas as a distinct CNS tumor subtype, characterized by recurrent loss of chromosome 3p21 and driven by various BAP1-inactivating alterations. Although rhabdoid morphology is present in some cases, it is not exclusive and should not be used as a grading criterion. Progression-free survival analysis showed a median of 21 months (95% CI: 12-NA), with a 2-year overall survival rate of 79% (95% CI: 60%-100%), highlighting the aggressive nature of these tumors. Gene expression profiling revealed upregulation of PRC target genes, dysregulated Polycomb signaling, and elevated expression in several cellular and growth factor pathways.BAP1-altered meningiomas represent a distinct and aggressive CNS tumor subtype associated with PRC dysregulation and recurrent 3p chromosome loss. These findings support the designation “meningioma, BAP1-altered.”